Novel variant in PNPLA6 gene causes Oliver-McFarlane syndrome in a Chinese family: 13 years follow-up - Xiao, Panpan; Gu, Yonghua; Qi, Xiaolong; Li, Ting; Zuo, Tingting; Xie, Yule; Zhang, Shuang; Sheng, Xunlun (Frontiers in Genetics, 2025)
IntroductionOliver-McFarlane syndrome (OMCS) is a rare autosomal recessive disorder characterized by trichomegaly, severe chorioretinal dystrophy, and multiple pituitary hormone deficiencies. Its marked genetic and clinical heterogeneity presents significant challenges for definitive diagnosis.MethodsIn this study, we initially evaluated a proband clinically diagnosed with OMCS, followed by genetic analysis using whole-exome sequencing (WES). Candidate pathogenic variants were validated via Sanger sequencing and familial co-segregation analysis.ResultsWES identified compound heterozygous variants in the PNPLA6 gene: a known missense variant (c.3241G>A, p.Gly1081Arg) and a novel missense variant (c.3461G>A, p.Arg1154His). Over a 13-year follow-up, multisystem involvement was observed, including progressive retinochoroidopathy, trichomegaly, growth retardation, and intellectual disability. Disease progression was evident, with severe exacerbation of retinochoroidopathy accompanied by newly developed pituitary hormone deficiencies and absent secondary sexual characteristics.DiscussionOur findings expand the pathogenic variant spectrum and clinical phenotypic landscape of OMCS. Given the early onset and progressive nature of retinal involvement, we propose that early intervention targeting the preservation of retinal pigment epithelium (RPE) and photoreceptor function may be clinically beneficial.